Factors Related with Complication Following Gastrectomy: Retrospective Analysis based on the Clavien–Dindo Classification System - Putranto, Agi Satria; Siahaya, Fransisca Janne (UI Scholars Hub, 2019)
Introduction. Surgical resection is the only curative treatment option in the management of gastric cancer. A study carried out and aimed to retrospectively analyze all complications following gastrectomy in accordance with severity of Clavien–Dindo classification, in addition to identify the related factors to postoperative complications. Method. The cross-sectional study enrolling a total of 35 patients with complete medical records who underwent gastrectomy in Cipto Mangunkusumo General Hospital Jakarta between January 2007 and December 2017. The complications and related factors were evaluated. Statistical analysis was employed to find out the correlation. Results. Of the 35 patients underwent gastrectomy at Cipto Mangunkusumo General Hospital Jakarta, the median age was 67, and 51.4% were female. Median of preoperative albumin was 3.0 g/dL, intraoperative blood transfusion was 217 mL and intraoperative blood loss was 500 mL. A total of 32 out of 35 subjects (91.4%) underwent partial gastrectomy and three total gastrectomy (8.6%). The incidence of severe complications (stage ≥IIIa) was 25.7% (n = 9). Those requiring surgical intervention caused by pneumothorax (5.7%), intra-abdominal bleeding (2.9%), anastomotic leakage (5.7%), duodenal stump leak (2.9%). Septic shock/death also found (8.5%). Age, intraoperative blood loss, and intraoperative blood transfusion were positively correlated with complication (p